Successful Closure of a Benign Refractory Tracheoesophageal Fistula Using an Over-the-Scope Clip after Failed Esophageal Stent Placement and Surgical Management - Nonthalee Pausawasdi; Chotirot Angkurawaranon; Tanyaporn Chantarojanasiri; Arunchai Chang; Wanchai Wongkornrat; Somchai Leelakusolvong; Asada Methasate (Korean Society of Gastrointestinal Endoscopy, 2020)
Tracheoesophageal fistulas (TEFs) have traditionally been managed surgically, but the endoscopic approach is widely performed as a less invasive alternative. Different closure techniques have been proposed with inconsistent results. An over-the-scope clip (OTSC) appears to be a reasonable option, but long-term results have not been well defined. We report the long-term outcomes of a complex case of successful closure of a benign refractory TEF using an OTSC after failed surgical management and esophageal stent placement.